2012
DOI: 10.1002/adma.201103832
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotubes Induce Bone Calcification by Bidirectional Interaction with Osteoblasts

Abstract: Multi‐walled carbon nanotubes (MWCNTs) promote calcification during hydroxyapatite (HA) formation by osteoblasts. Primary cultured osteoblasts are incubated with MWCNTs or carbon black. After culture for 3 weeks, the degree of calcification is very high in the 50 μg mL−1 MWCNT group. Transmission electron microscopy shows needle‐like crystals around the MWCNTs, and diffraction patterns reveal that the peak of the crystals almost coincides with the known peak of HA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 49 publications
1
54
0
1
Order By: Relevance
“…Another finding was that this activation was accompanied by the deposition of hydroxyapatite around the CNTs, which was catalyzed by alkaline phosphatase (ALP) released from osteoblasts. 218 These findings demonstrated that CNTs functioning as a scaffold interact with the body to promote osteogenesis and thereby the process of bone tissue regeneration. To date, no other scaffold has interacted with the body in this way; CNTs are expected to be breakthrough materials in regenerative medicine research as well.…”
Section: Present Status Of Research Into the Application Of Cnts As Bmentioning
confidence: 94%
See 1 more Smart Citation
“…Another finding was that this activation was accompanied by the deposition of hydroxyapatite around the CNTs, which was catalyzed by alkaline phosphatase (ALP) released from osteoblasts. 218 These findings demonstrated that CNTs functioning as a scaffold interact with the body to promote osteogenesis and thereby the process of bone tissue regeneration. To date, no other scaffold has interacted with the body in this way; CNTs are expected to be breakthrough materials in regenerative medicine research as well.…”
Section: Present Status Of Research Into the Application Of Cnts As Bmentioning
confidence: 94%
“…466 To assess the use CNTs as a possible bone tissue regeneration scaffold, we examined in detail their effects on osteoblasts (bone-forming cells) and osteoclasts (bone-absorbing cells), as described in section 2.3.2. 217,218 …”
Section: Present Status Of Research Into In Vitro Toxicity Of Cnts Fomentioning
confidence: 99%
“…In particular, CNTs have emerged as a promising functional nanomaterial for bone regeneration as they can promote osteogenesis of mesenchymal stem cells [5], as well as osteoblast functioning [6], and bone calcification [7]. Previous studies reported that extracellular matrix proteins adsorbed on CNTs mediate cell adhesion and subsequently remodel cell cytoskeleton [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] In addition, in closely related bioengineering fields, chemically modified CNTs alone or in combination with distinct composite materials have been applied to facilitate neuronal growth, cartilage, and myocardial tissue differentiation, among other applications. [20][21][22][23][24][25][26][27][28][29][30][31][32] Furthermore, CNTs in suspension have also been investigated as potential carriers for drug delivery, and have been shown to have no effect on vital functions of cells. 31,32 In the current work, we have evaluated the bone-inducing properties of carboxyl (COOH)-modified CNTs by conducting in vitro experiments on two models of progenitor cells, human fetal osteoblasts (hFOBs) and murine embryonic stem cells (mESCs), and we have further investigated bone induction in vivo in a rat model.…”
Section: Introductionmentioning
confidence: 99%